Long-term carvedilol therapy effects on left ventricular remodeling and glycemia in patients with chronic heart failure and Type 2 diabetes mellitus - R. R. Samedov; A. B. Bakhshaliev (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study the effects of long6term carvedilol treatment on left ventricular (LV) remodeling and glycemia control parameters in patients with chronic heart failure (CHF) due to post6infarction cardiosclerosis, and Type 2 diabetes mellitus (DM-2).Material and methods. This 12-month study included 30 patients with functional Class (FC) II-III CHF by NYHA classification, LV ejection fraction (EF) <40% and DM-2. Carvedilol was administered in the daily dose of 6,25-25 mg.Results. Carvedilol therapy was associated with substantial heart rate reduction: from 103,5±4,6 to 79,7±2,3 bpm (р<0,001). After 12 months, end-diastolic and end-systolic volumes decreased from 199,4±32,7 to 182,7±36,8and from 132,0±27,9 to 112,8±31,3 ml, respectively (р<0,001), LV EF increased from 34,22±3,80 to 39,04±5,39%. Carvedilol therapy did not affect glycemia levels: 178,0±12,97 mg/dl at baseline, 180,27±12,72 mg/dl in the end of the study (р>0,05).Conclusion. Long-term carvedilol therapy was associated with improved clinic and hemodynamic status, as well as delayed LV remodeling, without affecting glycemia levels in patients with CHF and DM-2.